Making of western Indology : Henry Thomas Colebrooke and the East India Company - Rocher, Rosane (Royal Asiatic Society books, 2012)
"For thirty years in India at the cusp of the eighteenth and nineteenth centuries, Henry Thomas Colebrooke was an administrator and scholar with the East India Company. This book explains and evaluates Colebrooke's position as the founder of modern Indology.The book discusses how Colebrooke embodies the significant passage from the speculative yearnings attendant on eighteenth century colonial expansion, to the professional, transnational ethos of nineteenth century intellectual life and scholarly enquiry. It covers his early career at the East India Company, and his role in the supreme council and as theorist of the Bengal government. The book highlights how his unprecedented familiarity with a broad range of literature established him as a leading scholar of Sanskrit and president of the Asiatic Society in Calcutta. Colebrooke went on to found the Royal Asiatic Society of Great Britain and Ireland, and has set the standards for the study of western Indology. Written by renowned academics in the field of Indology, and drawing on new sources, this biography is a useful contribution to the reassessment of Oriental studies that is currently taking place"--